Civil society organisations and the fight for rights in Brazil: analysis of an evolving context and future challenges. Issue 5 (3rd July 2016) - Mendonça, Patricia; Alves, Mário Aquino; Nogueira, Fernando
ABSTRACT: The operational environment of civil society organisations (CSOs) in Brazil has undergone several changes since the 1990s that deepened in the last decade, especially for a group of organisations that are the focus of this study: CSOs working for the promotion and defence of rights (AHRCSOs – advocacy and human rights CSOs). This article examines these recent changes, detailing the main limitations and conditions imposed on AHRCSOs by analysing their organisational and cultural characteristics. The organisational field of AHRCSOs is fluid and dispersed, and several organisations perform different activities. The article traces the history of these organisations and the foundations that led them to build their shared identity project. It then discusses AHRCSOs' organisational features and culture, in relation to the changes faced by the field and the challenges to be met. The closing remarks point to the need for changes in the culture and operations of these organisations in order to guarantee their sustainability of funding, as well as their capacity for social dialogue and intervention.